Design of wireless device to measure plantar pressure and gait analysis - Khatri, Mahendra; Dabadi, Sambardhan; Shrestha, Sandeep Kumar; Acharya, Saugat; Tamang, Sudip; Shakya, Swornima (Journal of Innovations in Engineering Education, 2019)
Foot plantar pressure is the pressure field that acts between the plantar region of the foot and supporting ground. The pressure exerted on the variable region of the foot can be determined using discrete pressure sensors. Information obtained from these sensors is useful in the measurement of gait and posture for diagnosing various problems associated with a lower limb, footwear design, and sports biomechanics. This project is aimed to design a portable in-shoe plantar pressure and gyroscope-based gait angle measurement system. Six Force Sensitive Resistor (FSR) placed in the sole (hallux, 1st, 5th metatarsal, midfoot lateral, midfoot medial and heel respectively) detects the plantar pressure and gyroscope placed at the ankle, knee and hip help measure the orientation and angle of joint movement during various phases of gait. The study among 16 male and 16 female subjects illustrated the significant pressure variation (p<0.0001, t=5.17 with α=95%). Similarly, there was a significant difference in pressure between normal and fast walking speed (p<0.0001, t=5.88) with mean values of 353Kpa and 426Kpa respectively. The mean pressure value for slow walking speed was 423Kpa while there was no significant variation between slow and normal walking speeds (p=0.62, t=1.98). Plantar pressure increased linearly with an increase in the body weight of a person as well. The mean pressure for the 45-50 age group was 313.25Kpa and that for 70-75 was 449Kpa. The study among 10 diabetics and 10 non-diabetic subjects illustrated significantly higher pressure on 1st and 5th metatarsal on diabetic subjects (p=0.0207 and t=2.536). The movement of ankle, knee and hip joint is visualized using the 3D model of a lower limb through processing software. The study illustrated the range of ankle joint movement between -60(dorsiflexion) to 200(plantarflexion), for knee joint was 00 to 300 (flexion) and that for hip joint was -50(extension) to 400(flexion). There was a significant difference in angular values for all three joints while climbing up and down the staircase as compared to walk in a level surface.